Optimalisasi Pengelolaan Media Sosial untuk Penguatan Citra dan Promosi Layanan Birojasa.official - Herista, Nasya Avrilia; Wajaya, Rama Adi; Rochmaniah, Ainur (Universitas Pahlawan Tuanku Tambusai, 2026)
This community service activity aims to optimize the management of the Official Service Bureau's social media accounts to strengthen its image and promote its services. The main issues faced by partners included a lack of consistent posting, a lack of structured content planning, and low Instagram account performance. The community service method was implemented through a five-stage mentoring approach: observation, planning, content production and editing, scheduling and publication, and evaluation. The results showed an increase in the number of posts from 374 to 392, an increase in followers from 49 to 57, and an increase in posting consistency and audience interaction. These findings confirm that a structured social media strategy contributes to strengthening the digital image and empowering partners independently and sustainably.